Population dynamics of Rainbow Sardines, Dussumieria acuta (Valenciennes, 1847) from Pakistani waters - Abdul Baset; Qun Liu; Baochao Liao; Abdul Waris; Han Yanan; Zhang Qingqing (International Journal of Aquaculture and Fishery Sciences - Peertechz Publications, 2020)
Length frequency data of Rainbow Sardines, Dussumieria acuta were collected and measured from the coast of Pakistan during 2015, ranging from 5 to 19 cm (total length). Weight ranges were measured from 2 to 64 g. The length frequency data were analysed for the estimation of population dynamics, so b was estimated at 2.70. The estimated von Bertalanffy growth function parameters of 19.95 cm (L∞) and 0.730 year-1 (K). The mortality rate Z= 1.84 year-1, M= 1.59 year-1 F= 0.25 year-1 and E= F/Z= 0.135. The yield-per-recruit analysis indicated that when tc was 1, Fmax was 1 year-1. Currently, the age at first capture is about 1 year and Fcurrent was 0.25 year-1. Therefore, Fcurrent was smaller than Fmax. With Gulland method, the biological reference point for fishery (Fopt) was estimated as 1.59 year1, which is also higher than current fish mortality. Therefore, the present study shows that the Dussumieria acuta fishery is safe in Pakistan.